DETERMINATION OF LEADERSHIP, COMMUNICATION, ACHIEVEMENT MOTIVATION OF LOYALTY THROUGH ORGANIZATIONAL CULTURE IN SAVE LOAN COOPERATIVE - Afrianti, Dewi; Wibisono, Chablullah; Sari, Ika Novita; Lubis, Mutia Amalia (International Journal of Psychosocial Rehabilitation, 2020)
Empowerment of Cooperatives is one of the achievements of the goals of the Indonesian nation-state, and according to the opening of the 1945 Constitution of the Republic of Indonesia is to advance public welfare. Its implementation uses the basis of the principle of kinship (article 33 paragraph 1) and the national economy’s operation based on economic democracy (article 33 paragraph 4). The lack of maximum performance of some cooperatives, in general, is caused by the low quality of human resources is none other than the low manager’s knowledge of cooperatives. In this study, the population is the members and administrators of Savings and Loan Cooperatives in Tanjung Pinang City as a whole. This study uses census techniques or saturated samples, meaning that the entire population will be the authors to make samples. In other words, the entire population will be the author uses without having to draw research samples. The total population to be used is 120 respondents. To test the hypothesis in this study, a multivariate analysis of Structural Equation Modeling (SEM) was used using the Amos version 24 computer program. The results of the study were obtained: Square Multiple Correlation values for Organizational Culture variable (culture) R2 = 0.386 is identical to R2 in SPSS of 0.386, then the amount of Determination is Square Multiple Correlation value for Organizational Culture variable times = 38.6%. Thus, it can be stated that the change in Organizational Culture is influenced by Leadership, Communication, and Achievement Motivation by 38.6%. For Loyalty (loyal) R2 = 0.430, the amount of Determination = 43%. Thus, it can be stated that Loyalty changes are influenced by Leadership, Communication and Achievement Motivation, and Organizational Culture by 43%. The problem of cooperatives in Tanjung Pinang has been answered with this research.